2021
DOI: 10.1186/s12941-021-00487-y
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanisms of fluoroquinolone resistance found in rectal swab isolates of Enterobacterales from men undergoing a transrectal prostate biopsy: the rationale for targeted prophylaxis

Abstract: Background Transrectal ultrasound-guided prostate biopsy (TRUS-Bx) is considered an essential urological procedure for the histological diagnosis of prostate cancer. It is, however, considered a “contaminated” procedure which may lead to infectious complications. Recent studies suggest a significant share of fluoroquinolone-resistant rectal flora in post-biopsy infections. Methods The molecular mechanisms of fluoroquinolone resistance, including PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This could be con rmed by the mutations found in these isolates, where double mutations occurring both in gyrA (D87N and S83F) and parC (T57S and S80I/S80R) lead to uoroquinolone-resistance in Salmonella strains. Of note, we found that only a single mutation in gyrA (D87Y) or parC (T57S) was associated with an elevated Minimum Inhibitory Concentration (MIC) value [45], however, not lead to uoroquinolone resistance in the remaining 34 isolates without PMQRs. Meanwhile, the presence of single mutation in the remaining 34 uoroquinolone-non-resistant strains also means that, once they acquired more mutations or PMQRs, resistance to uoroquinolone could be easily acquired, since PMQR determinants may result in an increase in mutations of topoisomerase [46].…”
Section: Discussionmentioning
confidence: 88%
“…This could be con rmed by the mutations found in these isolates, where double mutations occurring both in gyrA (D87N and S83F) and parC (T57S and S80I/S80R) lead to uoroquinolone-resistance in Salmonella strains. Of note, we found that only a single mutation in gyrA (D87Y) or parC (T57S) was associated with an elevated Minimum Inhibitory Concentration (MIC) value [45], however, not lead to uoroquinolone resistance in the remaining 34 isolates without PMQRs. Meanwhile, the presence of single mutation in the remaining 34 uoroquinolone-non-resistant strains also means that, once they acquired more mutations or PMQRs, resistance to uoroquinolone could be easily acquired, since PMQR determinants may result in an increase in mutations of topoisomerase [46].…”
Section: Discussionmentioning
confidence: 88%
“…Studies have suggested that the agricultural use of antimicrobial agents increased the number of human infections caused by drug-resistant bacteria [ 17 ]. Furthermore, consumption of food contaminated by PMQR-positive strains or use of FQs in ambulatory and hospital therapy may promote pre-selection factors for FQ resistance [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have previously investigated the range of post-TRUS-Bx complications in the context of FQ resistance. Recently, our team published a study on the molecular mechanisms of FQ-resistance including the gyrA , gyrB and parC , parE mutations and PMQRs of Enterobacterales from rectal swabs of 48 men undergoing transrectal prostate biopsy [ 12 ]. Until recently, little has been known about the molecular properties of E. coli as causative agents of post-biopsy infections.…”
Section: Introductionmentioning
confidence: 99%